IMPLEMENTATION OF AUGMENTED REALITY GPS TRACKING AS A GUIDE TO BUILDINGS AT PEMBANGUNAN PANCA BUDI UNIVERSITY - Mhd Rohid Alfahrizi; Heni Wulandari; Randi Rian Putra (Bahasa Indonesia, 2026)
At Pembangunan Panca Budi University, to find the location of a building, only signs and campus maps are used as navigation tools. This method makes it a little difficult for students, especially new students and visitors, to find the building they want to go to. The purpose of this study is to create an augmented reality application as a GPS-based building guide. This study uses the Multimedia Development Life Cycle (MDLC) method, which includes six phases: concept, design, material collecting, assembly, testing, and distribution. The MDLC approach was chosen because this method is suitable for developing interactive multimedia applications. The resulting application has navigation features to the destination building such as a minimap, distance estimation, and directions. The results of system testing using Blackbox testing indicate that all features can function properly. Therefore, this GPS-based augmented reality application is expected to help students, lecturers, and visitors in finding the building they are going to.